Retroperitoneal absceces and abdominal wall fascitis by complicated acute appendicitis: A case report - Vera-Portilla, Walter (2021)
The retroperitoneal abscess can be secondary to retrocecal appendicitis. We present the case of a 66 years old male, obese and diabetic, who presented with pain and lumbar mass, and a previous history of abdominal pain. A tomography showed a retroperitoneal abscess with soft tissue and a right scrotal bag. He was admitted to the operating room and a retrocecal appendix with distal end digested was evidenced, and when we opening the retroperitoneum and making a right lumbar and inguinal incision the pus leakage was showed too. The patient received antibiotic therapy and cures, and had a good evolution. Retroperitoneal abscess secondary to acute appendicitis is a rare and serious surgical infection, and it causes necrotizing fasciitis is exceptional. Therefore, it should be included within the diagnostic possibilities in allimmunosuppressed patients with low back pain and a history of abdominal pain; and they will required a CT scan.